Socialna država in solidarnost - Dragoš, Srečo (Teorija in praksa, 2016)
Even though Slovenia is situated below-average regarding the at-risk-of-poverty rate in the European Union and has relatively low income inequality, all indicators of the welfare state are unfavourable and worrying. The paper shows how Slovenian public opinion responds to this troublesome condition, particularly in relation to the prevalence of bonds of solidarity. These are not just above-reciprocal (a very rare phenomenon), but also reciprocal. Among them, we can distinguish two types of reciprocity: generalised and balanced. The main research question of this paper is what is happening with both types of bonds of solidarity in relation to changes in the welfare state. Comparing public opinion data on (the relationship to) solidarity and the share of wealth allocated to social protection, we can confirm the thesis that increased social protection is coinciding with smaller shares of balanced reciprocity in relation to generalised reciprocity, and vice versa. In the context of the modest or absent welfare state, people are forced to compensate access to important resources by developing balanced reciprocity because generalised reciprocity has a limited range when it comes to reducing risks.
Keywords: javno mnenje; liberalism; liberalizem; socialna država; socialna politika; solidarity; solidarnost; vrednote; welfare state